" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
4x-12-2x+6=8
2x-6 = 8
2x = 8+6
x = 14 : 7
x = 7
2.4x+3(x-2)-(5-4x)=0
4x+3x-6-5+4x=0
11x-11 = 0
11x = 11
x = 11/11
x = 1
3.3(2x-3)-2(x+1)=x-3
6x-9-2x-2 = x -3
6x-2x-x = -3+9+2
3x = 8
x = 8/3
4.8y-5(2y-3)=4(y-3)+18
8y-10y+15 = 4y-12+18
8y-10y-4y = -12+18-15
-7y = -9
y= 9/7
4x-12-2x+6 = 8
2x-6 = 8
2x = 14
x = 7
2..4x+3(x-2)-(5-4x)=0
4x+3x-6-5+4x = 0
11x = 11
x = 1
3.3(2x-3)-2(x+1)=x-3
6x-9-2x-2 = x-3
3x = 9
x = 3
4.8y-5(2y-3)=4(y-3)+18
8y-10y+15 = 4y-12+18
-6y = -9
y = 9/6
5.5(2y+4)-(10y-16)=6-4y
10y +20-10y+16=6-4y
4y = -30
y = -30/4
semoga membantu :)